Investigating the Effectiveness of Using Quillbot as a Paraphrasing Tool to Enhance EFL Students'Fluency in writing The Case of Third Year LMD Students of English at the University of Souk-Ahras - Imene BENNOUAR (My University, 2024)
Abstract The present study probed the effectiveness of using Quillbot as a paraphrasing tool to enhance 3 rd. year students’ fluency when they write in the Foreign Language (FL) classroom context. The research aimed to examine the impact of Quillbot on vocabulary enrichment, grammar mistakes’ reduction, and coherence development. Yet, a pre-experimental research is designed involving one experimental group consisting of 18 third year students at Mohamed Cherif Messaadia (MCM) University in Souk-Ahras during the academic year 2023-2024 chosen conveniently from 96 students. Additionally, this study employed a mixed-methods approach, combining quantitative and qualitative methods for comprehensive insights. Moreover, data collection tools embraced a questionnaire, a pre-test and a post-test to address the raised research questions and the set hypothesis. The findings unveiled that Quillbot application has a considerable and immediate impact on improving students’ writing fluency and enhancing their paraphrasing skills. ------------------- الملخص استكشفت الدراسة الحالية فعالية استخدام أداة إعادة الصياغة كويلبوت لتعزيز طلاقة طلاب السنة الثالثة عند الكتابة في سياق الفصول الدراسية للغة الأجنبية. هدفت الدراسة إلى فحص تأثير كويلبوت على إثراء المفردات، تقليل الأخطاء النحوية، وتطوير الترابط. تم تصميم بحث تجريبي أولي يتضمن مجموعة تجريبية واحدة تتكون من 18 طالبًا في السنة الثالثة بجامعة محمد شريف مساعدية في سوق أهراس خلال العام الدراسي 2023-2024، تم اختيارهم بشكل مريح من بين 96 طالبًا. بالإضافة إلى ذلك، استخدمت هذه الدراسة نهجًا مختلطًا، يجمع بين الطرق الكمية والنوعية للحصول على رؤى شاملة. علاوة على ذلك، شملت أدوات جمع البيانات استبيانًا، واختبارًا قبليًا واختبارًا بعديًا لمعالجة الأسئلة البحثية المطروحة والفرضية الموضوعة. كشفت النتائج أن تطبيق كويلبوت له تأثير كبير وفوري في تحسين طلاقة كتابة الطلاب وتعزيز مهارات إعادة الصياغة لديهم --------------------- Résumé Cette étude a exploré l'efficacité de l'utilisation de l'outil de reformulation Quillbot pour améliorer la fluidité des étudiants de troisième année lorsqu'ils écrivent dans le contexte de la classe de langue étrangère. L'objectif de la recherche était d'examiner l'impact de Quillbot sur l'enrichissement du vocabulaire, la réduction des erreurs grammaticales et le développement de la cohérence. Une recherche pré-expérimentale a été conçue, impliquant un groupe expérimental composé de 18 étudiants de troisième année à l'Université Mohamed Cherif Messaadia (MCM) à Souk-Ahras pendant l'année académique 2023-2024, choisis de manière pratique parmi 96 étudiants. De plus, cette étude a employé une approche mixte, combinant des méthodes quantitatives et qualitatives pour des insights complets. Les outils de collecte de données comprenaient un questionnaire, un pré-test et un post-test pour répondre aux questions de recherche soulevées et à l'hypothèse établie. Les résultats ont révélé que l'application Quillbot a un impact considérable et immédiat sur l'amélioration de la fluidité de l'écriture des étudiants et l'amélioration de leurs compétences en reformulation